Structure analysis and antioxidant activities of an amylopectin-type polysaccharide isolated from dried fruits of Terminalia chebula - Jeong, Hye Kyoung; Lee, Dongjoo; Kim, Hong Pyo; Baek, Seung Hoon (Carbohydrate Polymers, 2019)
Dried fruits of Terminalia chebula (TF) are used as herbal medicine for diverse symptoms, and their bioactivities are known to involve antioxidant activities. The aim of this study was to elucidate the structure and antioxidant effects of an active TF polysaccharide (TFP). The neutral polysaccharide (named as TFP-a) isolated by ion-exchange chromatography was a homogenous α-Glc-rich polysaccharide (over 70% α-Glc, 534.9 kDa, PDI 1.36) with a porous and flake-like morphology. Linkage and NMR data comprehensively showed that TFP-a was an amylopectin-type polysaccharide with (1→4)-α-Glc(p) backbone branched at C6/C2. Side chains were composed of (1→4)-β-Gal(p) substituted with α-Ara(f), β-GalUA(p), β-GalUA(p)-Me, and α-Rham(p). In antioxidant activity assays, TFP-a exhibited potent and concentration-dependent antioxidant effects, including DPPH and superoxide radical scavenging and reducing power. We concluded that TFP-a is an amylopectin-type polysaccharide that may be used as a potential natural antioxidant.
Keywords: Anti-oxidant activities; Antioxidant effect; Concentration-dependent; Ion exchange chromatography; Natural antioxidants; Structure analysis; Superoxide radical; Terminalia chebula; Amylopectin; Antioxidants; Biphenyl Compounds; Fruit; Molecular Structure; Picrates; Superoxides; Terminalia; Amylopectin; Antioxidant activity; Polysaccharide; Terminalia chebula